Space–Time method for flow computations with slip interfaces and topology changes (ST-SI-TC). (15th December 2016) - Takizawa, Kenji; Tezduyar, Tayfun E.; Asada, Shohei; Kuraishi, Takashi
Highlights: ST-SI and ST-TC methods are integrated in the framework of the ST-VMS method. ST-SI is a moving-mesh method that can handle flow around spinning solid surfaces. ST-TC is a moving-mesh method that can handle flows with topology changes. The combination can handle a rotating solid surface in contact with a solid surface. Successful computations of tire models with road contact and prescribed deformation. Abstract: The Space–Time Variational Multiscale (ST-VMS) method was introduced to function as a moving-mesh method. It is the VMS version of the Deforming-Spatial-Domain/Stabilized ST (DSD/SST) method. It has reasonably good turbulence modeling features and serves as a core computational method. The ST Slip Interface (ST-SI) method was introduced to addresses the challenge involved in high-resolution representation of the boundary layers near spinning solid surfaces. The mesh covering a spinning solid surface spins with it and thus maintains the high-resolution representation near it. The ST-TC method was introduced for moving-mesh computation of flow problems with topology changes, such as contact between solid surfaces. It deals with the TC while maintaining high-resolution boundary layer representation near solid surfaces. The "ST-SI-TC" method we introduce here integrates the ST-SI and ST-TC methods in the ST-VMS framework. It enables accurate flow analysis when we have a spinning solid surface that is in contact with a solid surface. We present two test computations with the ST-SI-TC method, and they are both with models of flow around a rotating tire with road contact and prescribed deformation, one with a 2D model, and one with a 3D model.